Brain Network Integrity Changes in Subjective Cognitive Decline: A Possible Physiological Biomarker of Dementia - Fogel, Hilla; Levy-Lamdan, Ofri; Zifman, Noa; Hiller, Tal; Efrati, Shai; Suzin, Gil; Hack, Dallas C.; Dolev, Iftach; Tanne, David (Frontiers in Neurology, 2021)
Objective: The current study seeks to illustrate potential early and objective neurophysiological biomarkers of neurodegenerative cognitive decline, by evaluating features of brain network physiological performance and structure utilizing different modalities. Methods: Study included 17 clinically healthy individuals with self-reported cognitive decline (Subjective Cognitive Decline group, SCD, no objective finding of cognitive decline), 12 individuals diagnosed with amnestic Mild Cognitive Impairment (aMCI), 11 individuals diagnosed with Dementia and 15 healthy subjects. All subjects underwent computerized cognitive performance testing, MRI scans including T1 for grey matter (GM) volume quantification, DTI for quantification of white matter (WM) microstructure fractional anisotropy (FA) and mean diffusivity (MD), and brain network function evaluation using DELPHI (TMS-EEG) measures of connectivity, excitability and plasticity. Results: Both DELPHI analysis of network function and DTI analysis detected a significant decrease in connectivity, excitability and WM integrity in SCD group compared to healthy control (HC) subjects, a significant decrease was also noted for aMCI and Dementia groups compared to HC. In contrast, no significant decrease was observed in GM volume in SCD group compared to healthy norms, a significant GM volume decrease was observed only in objectively cognitive impaired aMCI subjects and in dementia subjects. Conclusions: This study results suggest that objective direct measures of brain network physiology and WM integrity may provide early-stage biomarkers of neurodegenerative related changes in subjects that have not yet displayed any other objective measurable cognitive or GM volume deficits which may facilitate early preventive care for neurodegenerative decline and dementia.